2016
DOI: 10.1038/srep28382
|View full text |Cite
|
Sign up to set email alerts
|

Altered multisensory temporal integration in obesity

Abstract: Eating is a multisensory behavior. The act of placing food in the mouth provides us with a variety of sensory information, including gustatory, olfactory, somatosensory, visual, and auditory. Evidence suggests altered eating behavior in obesity. Nonetheless, multisensory integration in obesity has been scantily investigated so far. Starting from this gap in the literature, we seek to provide the first comprehensive investigation of multisensory integration in obesity. Twenty male obese participants and twenty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
33
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 76 publications
6
33
1
Order By: Relevance
“…This dissimilarity supports the findings of previous studies suggesting the existence of sensory integration deficiencies between obese and normal weight subjects [9, 10, 12, 13, 15]. It remains to be seen if these sensory integration problems exist prior to obesity and can be seen as a contributing factor to becoming obese or whether the development of obesity leads to detrimental consequences for the sensory integration process.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This dissimilarity supports the findings of previous studies suggesting the existence of sensory integration deficiencies between obese and normal weight subjects [9, 10, 12, 13, 15]. It remains to be seen if these sensory integration problems exist prior to obesity and can be seen as a contributing factor to becoming obese or whether the development of obesity leads to detrimental consequences for the sensory integration process.…”
Section: Discussionsupporting
confidence: 88%
“…As fine motor skills are not directly affected by excess mass, this would suggest that other factors exist to impede obese individual's motor control [13]. This leads to the suggestion that the problem may lie in the sensory integration process [9, 10, 12, 13, 15]. …”
Section: Introductionmentioning
confidence: 99%
“…Critically, more recent studies suggest that an enlarged body might affect not only the subjective representation of bodily dimensions, meaning how people perceive the dimensions of their body parts, but also the perception of sensory bodily input; the perception of the intensity of peripheral pain [14][15][16], vibratory sensation and temperature [17],sense of satiety [18] and gastric motor functions [19] seem to be altered in obesity. Moreover, it was recently reported that people affected by obesity show alterations in the successful integration of multiple sensory input, such as audio-tactile stimuli [20] and audio-visual stimuli [21],anessential cognitive sensory process for successful actions in the environment. Consider the common behavior of walking: it results from a complex and unaware integration of different sources of information [22],suchas postural and sensory inputs related to the physical body size [23],dimensions and spatial position of possible obstacles [24],relationships between gait parameters and body proportions [25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Deviations in the temporal binding of multisensory stimuli have farstretching implications. A widened TBW, for example, leads to over-integration of stimuli and has been associated with a variety of clinical conditions, such as autism spectrum disorders, schizophrenia, dyslexia, and obesity Scarpina et al 2016;. In contrast, a narrow TBW has been linked to enhanced performance in both verbal and non-verbal problem solving tasks (Zmigrod and Zmigrod 2016) and individuals with a narrow TBW are less prone to be deceived by multisensory illusions, both when presented with simple perceptual and more dynamic stimuli (Stevenson et al 2012).…”
Section: Discussionmentioning
confidence: 99%